A Psychoanalytic Reading of Esther in The Bell Jar - Tian, Yujie (Cultural and religious studies, 2022)
By adopting Freudian psychoanalysis, this paper attempts to verify that in Sylvia Plath’s The Bell Jar Esther is traumatized by her father’s premature death and her mother’s lack of empathy, which leave her feeling abandoned, and therefore result in the core issues of fear of abandonment and fear of intimacy. Esther’s whole pattern of psychological behavior, mainly manifested in her relationship with others, is grounded in her unconscious conviction that emotional ties to another human being will lead to one’s being emotionally abandoned.